Synthesis, Free Solution Capillary Electrophoresis Separation and Toxicity of Seven Potential Impurities of Dobutamine - Pallavicini, Marco; Pezzetta, Daniele; Rossoni, Giuseppe; Valoti, Ermanno; Villa, Luigi (Arzneimittelforschung, 2001)
The seven O-methylated analogs of dobutamine ((±)-4-[2-[[3-(p-hydroxyphenyl)1-methylpropyl]amino]ethyl]pyrocatechol, CAS 34368-04-2), a trihydroxy secondary amine, can be considered potential impurities of the latter, the ultimate step of the synthesis of dobutamine being the deprotection of the three phenolic groups. In order to enable the detection and the identification of such a contamination, the di- and the monomethylated derivatives of dobutamine were prepared and their mixture with dobutamine and its trimethoxy precursor completely resolved by Free Solution Capillary Electrophoresis (FSCE). Indeed, the above impurities proved to occur in dobutamine in consequence of improper demethylation conditions and to be significantly more toxic than the latter.
Keywords: CAS 34368-04-2; Dobutamine, O-methylated analogs, potential impurities, separation, synthesis, toxicity